Prevalence and correlates of hypertension among a nationally representative population-based sample of older adults in India in 2017-2018 - Karl Peltzer (2022)
In this study we aimed to determine the prevalence and correlates of hypertension in older adults in India. The cross-sectional sample consisted of 52,393 individuals (≥50 years) from the Longitudinal Ageing Study in India (LASI) Wave 1 in 2017-2018. Hypertension was defined as "systolic BP ≥140 mm Hg and/or diastolic BP ≥90 mm Hg or where the participant is currently on antihypertensive medication." Results indicate that the prevalence of hypertension was 45.4%, 48.0% among women and 42.3% among men. In adjusted logistic regression analysis, older age, higher education, urban residence, Muslims and Sikhs, overweight/obesity, arthritis, diabetes, angina and heart disease were positively associated with hypertension, while male sex, underweight, and vigorous physical activity were negatively associated with hypertension. In addition, in unadjusted analysis, higher subjective socioeconomic status, Muslims, and high cholesterol were positively and current tobacco use negativey associated with hypertension. Almost one in two older adults in India had hypertension. Several risk factors were identified, which can be targeted in public health interventions.